A high-magnification low overpotential magnesium battery boron-based electrolyte and a preparation method thereof
Patent Information
- Application Number
- CN202611360379.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]针对现有技术存在的上述不足,本申请提供了高倍率低过电位镁电池硼基电解液及其制备方法,本申请选择低成本的具有B-N键的硼基化合物-吗啉硼烷作为路易斯酸,与EtMgCl通过路易斯酸碱反应生成新型含B-N键活性阴离子的镁电解液,有利于Mg2+的脱溶剂化,增强了SEI的刚性,降低了界面阻抗,有利于拓宽硼氢类电解液的电化学窗口,赋予镁电池在高电流密度下的超长循环性能,从而解决现有技术中镁电解液的沉积/溶出过电位大、镁负极钝化、氧化稳定性低和倍率性能差的问题
[0017] 1. This application discovers that using ethyl magnesium chloride as a Lewis base magnesium source allows the free chloride ions to partially conduct current and simultaneously generate a specific adsorption effect on the magnesium anode surface, which can disrupt the formation of the insulating passivation layer to a certain extent. Introducing a morpholine borane complex into this system allows the boron-based component to undergo dipole-dipole and ion-dipole interactions with ether solvents and magnesium ions, respectively, weakening the interactions between magnesium and chloride and magnesium and ether solvents, loosening the solvation structure of magnesium ions, lowering the desolvation energy barrier of magnesium ions, and accelerating the interfacial ion transport rate. Furthermore, when an excess of morpholine borane is used, it can adsorb at the magnesium anode interface and preferentially undergo decomposition reactions, constructing a composite solid electrolyte interfacial membrane containing both inorganic and organic components and BN and CN bonds. This enhances the structural rigidity of the interfacial membrane and the electrostatic attraction of magnesium active cations, effectively reducing interfacial impedance. In addition, morpholine borane can also act as a water trap, inhibiting the passivation behavior of trace amounts of water in the electrolyte on the magnesium anode.
Smart Images

Figure CN122889838A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of magnesium-ion battery technology, specifically to a high-rate, low-overpotential magnesium battery boron-based electrolyte and its preparation method. Background Technology
[0002] Non-aqueous magnesium batteries benefit from abundant magnesium resources (approximately 2.1% of the Earth's crust) and high theoretical volumetric capacity (3833 mAh cm⁻¹). -3 Large theoretical mass capacity (2205 mAh g) -1 Furthermore, it is not prone to forming dendrites that penetrate the diaphragm during charging and discharging, thus exhibiting excellent safety. It is the most promising energy storage system in the "post-lithium era" and is particularly suitable for large-scale renewable energy storage scenarios.
[0003] However, despite the significant advantages of magnesium batteries in terms of theoretical performance and safety, their practical application is still severely limited by the bottleneck of the electrolyte system. This is because Mg... 2+ With its high charge density and strong Coulomb interaction, its solvation and migration processes in the electrolyte are far more efficient than those of monovalent Li ions. + The complex structure of magnesium leads to slow ion diffusion, limited electrode interface reactions, and frequent irreversible side reactions. Due to magnesium's low standard reduction potential (-2.37 V vs. SHE), many solvents and conventional Lewis bases readily undergo reduction reactions upon contact with the magnesium anode. The reaction products form a dense, non-ion-conducting passivation layer on the electrode surface, blocking ion migration pathways and ultimately rendering the magnesium deposition and dissolution processes irreversible. These problems result in short cycle life, low coulombic efficiency, and insufficient electrochemical stability in magnesium metal batteries. Designing a method to form Mg at the Mg anode interface is crucial. 2+ Electrolytes for conductive SEI films are crucial for the further development of rechargeable magnesium metal batteries. While Grignard reagents can deposit magnesium well, they are highly nucleophilic, sensitive to air, and have poor safety. Non-nucleophilic magnesium electrolytes (such as Mg(BH4)2, Mg(HMDS)2, Mg(TFSI)2, MgCl2, and Mg[B(ORF)4]2) are gradually becoming mainstream. Among them, boron-based electrolytes, represented by Mg[B(hfip)4]2, have become the benchmark due to their large-volume, weakly coordinated anion structure, charge delocalization, weak coordination, and high oxidation stability; however, they are expensive to produce, complex to synthesize, and have poor high-rate cycling performance. Another boron-magnesium salt, Mg(BH4)2, has limited solubility and coulombic efficiency in ether solvents and low oxidation stability, which also limits its practical application. Summary of the Invention
[0004] To address the aforementioned shortcomings of existing technologies, this application provides a high-rate, low-overpotential magnesium battery boron-based electrolyte and its preparation method. This application selects a low-cost boron-based compound with BN bonds—morpholinoborane—as a Lewis acid, which reacts with EtMgCl via a Lewis acid-base reaction to generate a novel magnesium electrolyte containing BN bond-containing active anions, thus benefiting Mg… 2+ The desolvation process enhances the rigidity of the SEI and reduces the interfacial impedance, which helps to broaden the electrochemical window of boron-hydrogen electrolytes and endows magnesium batteries with ultra-long cycle performance at high current densities. This solves the problems of large deposition / dissolution overpotential, magnesium anode passivation, low oxidation stability and poor rate performance in existing magnesium electrolytes.
[0005] To achieve the above objectives, in a first aspect, this application provides a boron-based electrolyte for high-rate, low-overpotential magnesium batteries, wherein the electrolyte is composed of a morpholine borane complex, a Lewis base, and an organic solvent; wherein the structural formula of the morpholine borane complex is as follows:
[0006] ;
[0007] In the organic solvent, the concentration of Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of morpholine borane complex is 0.15 mol / L to 0.9 mol / L.
[0008] Preferably, the morpholine borane complex is morpholine borane.
[0009] Preferably, the Lewis base is ethyl magnesium chloride.
[0010] Preferably, the organic solvent is at least one selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, or 2-methyltetrahydrofuran.
[0011] Secondly, this application provides a method for preparing a boron-based electrolyte for a high-rate, low-overpotential magnesium battery. The specific steps for preparing the aforementioned boron-based electrolyte for a high-rate, low-overpotential magnesium battery are as follows:
[0012] After mixing and stirring Lewis base and organic solvent under an inert gas atmosphere, morpholine borane complex is added and stirred evenly to obtain the boron-based electrolyte for high-rate, low-overpotential magnesium battery.
[0013] In the organic solvent, the concentration of the Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of the morpholine borane complex is 0.15 mol / L to 0.9 mol / L; the molar ratio of the morpholine borane complex to ethyl magnesium chloride is (2:1) to (1:3).
[0014] Preferably, the morpholine borane complex, Lewis base, and organic solvent are pretreated to ensure that the water content and oxygen content in the mixture are <0.01ppm and <0.01ppm, respectively.
[0015] Thirdly, this application provides an application of a high-rate, low-overpotential magnesium battery boron-based electrolyte, wherein the aforementioned high-rate, low-overpotential magnesium battery boron-based electrolyte or the high-rate, low-overpotential magnesium battery boron-based electrolyte prepared by the aforementioned preparation method is used to prepare a rechargeable magnesium-ion battery.
[0016] Compared with the prior art, this application has the following beneficial effects:
[0017] 1. This application discovers that using ethyl magnesium chloride as a Lewis base magnesium source allows the free chloride ions to partially conduct current and simultaneously generate a specific adsorption effect on the magnesium anode surface, which can disrupt the formation of the insulating passivation layer to a certain extent. Introducing a morpholine borane complex into this system allows the boron-based component to undergo dipole-dipole and ion-dipole interactions with ether solvents and magnesium ions, respectively, weakening the interactions between magnesium and chloride and magnesium and ether solvents, loosening the solvation structure of magnesium ions, lowering the desolvation energy barrier of magnesium ions, and accelerating the interfacial ion transport rate. Furthermore, when an excess of morpholine borane is used, it can adsorb at the magnesium anode interface and preferentially undergo decomposition reactions, constructing a composite solid electrolyte interfacial membrane containing both inorganic and organic components and BN and CN bonds. This enhances the structural rigidity of the interfacial membrane and the electrostatic attraction of magnesium active cations, effectively reducing interfacial impedance. In addition, morpholine borane can also act as a water trap, inhibiting the passivation behavior of trace amounts of water in the electrolyte on the magnesium anode.
[0018] 2. This application also found that there is a synergistic effect between the above-mentioned solvation structure optimization effect and interface regulation effect. On the one hand, they jointly reduce the overpotential of magnesium deposition / dissolution process, and on the other hand, they broaden the oxidation stability window of the electrolyte, so that the battery can still maintain excellent cycle stability and rate performance under high current density conditions. At the same time, the electrolyte described in this application can be prepared by stirring at room temperature. The reaction conditions are mild, the process is simple, and the raw material cost is low, which makes it easy to realize industrial scale-up production.
[0019] 3. This application experimentally demonstrates that the Mg||Mg symmetric cell assembled using this electrolyte achieves a voltage of 0.1 mA·cm⁻¹. -2 and 0.05mAh・cm -2 Under test conditions, the initial overpotential was as low as 30 mV, and after 3200 cycles, it only slowly increased to about 70 mV; at 2 mA·cm -2 and 1 mAh・cm -2Under high current density conditions, the initial overpotential stabilized at 160 mV, and after 1000 h of cycling, it only increased to 240 mV. The Mg||Mo asymmetric cell assembled using this electrolyte achieved high current density at 0.1 mA·cm⁻¹. -2 The average overpotential under low current conditions is 127 mV, and at 5.0 mA·cm⁻¹... -2 The first-cycle overpotential is only 284 mV even at ultra-high current densities, effectively solving the technical problems of high deposition / dissolution overpotentials and polarization surges under high currents in existing magnesium electrolytes. Meanwhile, the morpholinoborane complex has a low LUMO molecular orbital energy level, enabling preferential reduction and decomposition at the negative electrode interface to construct a composite solid electrolyte interface film with both inorganic and organic components. This interface film possesses higher structural rigidity and ion conductivity, maintaining efficient magnesium ion cross-interface transport while preventing direct contact between the electrolyte and the negative electrode and suppressing irreversible side reactions, thus ensuring interface stability during long-cycle battery operation. Corresponding test data show that the Mg||Mo asymmetric battery achieves this at 0.1 mA·cm⁻¹. -2 and 0.05 mAh・cm -2 Under certain conditions, it can stably cycle for over 2300 times, with an average coulombic efficiency exceeding 99.7%; at 5.0 mA·cm⁻¹ -2 and 2.5 mAh・cm -2 Even under high current density conditions, it can still stably cycle for over 1000 cycles, maintaining an average coulombic efficiency of 99.8%, effectively improving the shortcomings of existing electrolytes such as short cycle life and rapid capacity decay at high currents. The aforementioned solvation structure regulation and interfacial film modification exhibit a positive synergistic effect. The reduction of the desolvation energy barrier provides a kinetic basis for the rapid transport of magnesium ions, while the stable and highly conductive interfacial film provides a continuous interfacial channel for ion transport during long cycles. The combined effect of these two factors endows the electrolyte with excellent rate tolerance and a wider electrochemical window. Experimental data show that this electrolyte can withstand a maximum rate of 10 mA·cm⁻¹. -2 The current density shock, symmetrical cell at 10.0 mA·cm -2 The overpotential at the current density was only 490 mV with no short circuit observed throughout the process; linear voltammetry results showed that the oxidation initiation potential of this electrolyte on the molybdenum current collector could reach 3.10 V vs. Mg. 2+ The oxidation stability of Mg was significantly improved; the assembled Mg||CuS full cell showed good oxidation stability at 50 mA·g. -1 The discharge specific capacity reaches 246 mAh·g at current density. -1 The current density was increased to 200 mA·g -1 It can still maintain 102 mAh・g -1 The discharge specific capacity, the current recovers to 50 mA·g -1The capacity can be restored to 235mAh·g. -1 It exhibits good rate reversibility. Attached Figure Description
[0020] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The coulombic efficiency (5 mA cm⁻¹) of magnesium deposition / dissolution on a Mo current collector for the electrolyte prepared in Example 1 of this application. -2 and 2.5 mAh cm -2 ( ) and specific capacity-voltage curve.
[0022] Figure 2 Linear scan voltammetry of the electrolyte prepared in Example 1 of this application on different working electrodes.
[0023] Figure 3 The Mg||Mg symmetric cell with electrolyte prepared in Example 1 of this application operates at 2 mA / cm². 2 Long-cycle performance at current density.
[0024] Figure 4 Magnesium deposition-dissolution curves of a Mg||Mg symmetric button cell with the electrolyte prepared in Example 1 of this application at different current densities. Detailed Implementation
[0025] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments used are not specified, they can be obtained commercially.
[0026] Unless otherwise specified in the specific circumstances, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within those ranges, and are not limited to the specific values listed when defining the range. For numerical ranges, endpoint values of various ranges, endpoint values of various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The term "and / or" used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B. Terms such as "about," "substantially the same," and similar expressions herein indicate that reasonable deviations are permissible.
[0027] I. A boron-based electrolyte for high-rate, low-overpotential magnesium batteries
[0028] To address the problems of high deposition / dissolution overpotentials, easy passivation of the magnesium anode, insufficient cycle stability and rate performance at high current densities in existing magnesium battery electrolytes, and the high cost and complex preparation process of existing high-performance boron-based electrolytes, this application focuses on the mainstream technology of boron-based electrolytes, aiming to optimize the magnesium ion solvation environment and anode interface characteristics. A boron ion complex with a boron-nitrogen hexacyclic coordination structure was discovered as a functional component, combined with ethyl magnesium chloride as a Lewis base magnesium source. These components were dispersed in an ether-based organic solvent, and a novel boron-based magnesium electrolyte system was constructed through Lewis acid-base interactions under room temperature stirring. This allows for the regulation of the magnesium ion solvation structure and anode interface film formation behavior. The electrolyte described in this application consists of a morpholine borane complex, a Lewis base, and an organic solvent; the structural formula of the morpholine borane complex is as follows:
[0029] ;
[0030] In the organic solvent, the concentration of Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of morpholine borane complex is 0.15 mol / L to 0.9 mol / L.
[0031] This application has yielded many unexpected technical effects after practical application: Mg||Mo asymmetric cells assembled using the electrolyte prepared in this application achieve a performance of 5.0 mA・cm -2 2.5 mAh·cm -2 Under high current density testing conditions, it can stably cycle for over 1000 cycles with an average coulombic efficiency of 99.8%. The deposition / dissolution overpotential in the first cycle is only 284 mV, and the overpotential remains at a low level even after 1000 cycles. When assembling Mg||Mg symmetric cells, at 2 mA·cm⁻¹ -2 1 mAh·cm -2It can be stably cycled for over 1000 hours at a current density, with a gradual increase in overpotential during cycling and no short circuits occurring throughout the cycle; after assembling a Mg||CuS full cell, the current density increases from 50 mA·g. -1 Increased to 200 mA・g -1 It can still maintain 102 mAh・g -1 The discharge specific capacity is high, and the specific capacity can be fully recovered after the current returns to the initial level. However, conventional boron-based magnesium electrolytes usually cannot simultaneously achieve long cycle life, high coulombic efficiency, and low overpotential at high current densities, and often require complex synthesis processes and multi-component compounding to achieve limited performance improvement. The electrolyte system constructed in this application can achieve a balance of low polarization, high reversibility, and long cycle life under high current conditions through a simple room temperature reaction of two components.
[0032] In some embodiments of this application, the morpholine borane complex is morpholine borane (amine borane, or 1,4-oxonium hexacyclic borane). In the screening of boron-based functional components, this application selects morpholine borane as the core boron source, rather than the simple borohydrides or bulky fluoroborate boron-based components commonly used in the prior art. This is because this application found that while simple borohydrides such as magnesium borohydride can achieve a certain deposition / dissolution coulombic efficiency, their oxidation stability window is narrow, making them difficult to adapt to higher voltage cathode systems; while bulky fluoroborates possess excellent oxidation stability and weak coordination characteristics, their raw material costs are high, their synthesis and preparation processes are complex, their large-scale application is difficult, and their cycle stability is poor. Morpholine borane, as a boron-nitrogen bond-containing borane complex, can participate in Lewis acid-base interactions within the system, forming a large-volume active borohydride anion structure with weak coordination characteristics with magnesium ions. This weakens the strong coulombic interaction between magnesium ions and anions, reduces the desolvation energy barrier of magnesium ions, and thus reduces the polarization overpotential of the magnesium deposition / dissolution process. In addition, morpholinoborane can capture trace amounts of water in the electrolyte, preventing passivation of magnesium metal. It can also preferentially undergo reduction decomposition at the magnesium anode interface, forming a composite solid electrolyte interfacial film containing inorganic and organic heterocyclic components. This interfacial film possesses higher structural rigidity and ion conductivity, effectively blocking direct contact between the electrolyte and the magnesium anode, suppressing irreversible side reactions and the formation of an insulating passivation layer, thus solving the problems of easy passivation and poor cycle stability of the magnesium anode. Furthermore, this application also discovered a positive synergistic effect between the solvation structure regulation and interfacial film formation. Optimization of the solvation structure reduces the kinetic resistance of the interfacial reaction, allowing magnesium ions to pass through the interfacial film more efficiently for deposition and dissolution. A stable interfacial film can maintain unobstructed ion transport channels during long cycles, preventing the interfacial impedance from continuously increasing with cycling. The combined effect of these two factors allows the electrolyte to maintain low polarization and long cycle life even at high current densities.
[0033] In some embodiments of this application, the Lewis base is ethyl magnesium chloride. Ethyl magnesium chloride is chosen in this application, rather than chloride-free magnesium salts or simple inorganic magnesium chloride. This is because chloride-free magnesium salts, such as magnesium bis(trifluoromethanesulfonyl)imide, while exhibiting good oxidative stability, lack the coordination assistance of chloride ions, resulting in strong binding between magnesium ions and the solvent, high desolvation resistance, and high deposition / dissolution overpotentials. Meanwhile, simple inorganic magnesium chloride has limited solubility in ether solvents, easily leading to insufficient ionic conductivity of the electrolyte and difficulty in achieving uniform interface regulation. Ethyl magnesium chloride, as an organic magnesium chloride, can achieve good solubility in ether solvents, ensuring the homogeneity and basic ionic conductivity of the electrolyte system. Its chloride ions possess strong Lewis basicity, which can participate in the coordination structure of magnesium ions, weakening the strong binding between the solvent and magnesium ions, alleviating the kinetic hindrance caused by strong solvation effects, and thus reducing the interfacial reaction overpotential. Meanwhile, chloride ions can generate a specific adsorption effect on the magnesium anode surface, inhibiting the reduction and decomposition of solvent molecules on the anode surface, reducing the formation of insulating passivation products, and improving the reversibility of magnesium deposition / dissolution. The bulk coordination and interfacial adsorption of chloride ions support each other. Bulk coordination optimizes the ion's form and transport characteristics, while interfacial adsorption inhibits side reactions from the reaction pathway. Together, they improve the reversibility of electrolyte cycling. At the same time, ethyl magnesium chloride can undergo a Lewis acid-base reaction with morpholine borane to jointly construct an active magnesium ion coordination structure. This, combined with the solvation regulation effect of boron-nitrogen anions, forms a synergistic effect, further weakening the solvation effect of magnesium ions and accelerating interfacial reaction kinetics.
[0034] In some embodiments of this application, the organic solvent is at least one selected from ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, or 2-methyltetrahydrofuran. This application uses these organic solvents, rather than other types of organic solvents such as carbonates or sulfones. This is because carbonate solvents are prone to irreversible reduction at the low reduction potential of the magnesium anode, forming a dense, non-conductive passivation layer that causes magnesium deposition / dissolution to lose its reversibility; while sulfone solvents, although exhibiting excellent oxidative stability, have high viscosity, which increases ion transport resistance and deteriorates rate performance. The ether solvents used in this application exhibit good reduction stability for magnesium anodes, reducing reduction side reactions on the anode surface and adapting to the operating potential range of magnesium metal anodes. Simultaneously, these ether solvents possess moderate electron-donating ability and their coordination strength with magnesium ions is within an appropriate range, ensuring sufficient dissolution of magnesium salts and boron-based components without forming an excessively strong solvated sheath layer. This provides a feasible basis for the moderate-strength coordination and solvation structure control of electron-delocalized boron-nitrogen anions. Furthermore, these ether solvents generally have low viscosity, ensuring high ionic conductivity and ion migration rate in the electrolyte, supporting charge-discharge processes at high current densities. The reducing stability, coordination characteristics, and viscosity characteristics of the solvent described in this application work synergistically. Suitable reducing stability is a prerequisite for the long-term stable operation of the electrolyte, moderate coordination strength provides room for regulation of solvation structure optimization, and low viscosity ensures the bulk transport efficiency of ions. The three factors work together with magnesium salt and boron-based functional components to achieve full-link optimization of solvation structure-interfacial film-bulk transport, ultimately endowing the electrolyte with excellent comprehensive electrochemical performance.
[0035] In some embodiments of this application, the concentration of Lewis base is 0.1 mol / L to 0.4 mol / L. When the concentration of ethyl magnesium chloride is below 0.1 mol / L, the amount of magnesium ions that can participate in migration in the system is insufficient, and the concentration of free chloride ions is also low. On the one hand, this leads to a decrease in the overall ionic conductivity of the electrolyte, a significant increase in the internal resistance of the battery, and a sharp increase in polarization at high current densities, making it difficult to support high-rate charge and discharge processes. On the other hand, chloride ions cannot form a sufficient adsorption coating layer on the magnesium anode surface, making it difficult to suppress the reduction and decomposition of solvent molecules on the anode surface. The formation of the insulating passivation layer cannot be effectively curbed, ultimately resulting in a decrease in the reversibility of magnesium deposition / dissolution and a shortened cycle life. When the concentration of ethyl magnesium chloride exceeds 0.4 mol / L, the total concentration of magnesium and chloride ions in the system becomes too high, promoting the formation of a large number of highly polymerized solvated ion clusters. This reduces the transport number of magnesium ions, increases ion transport resistance, and weakens the rate performance of the electrolyte. Simultaneously, the excessively high chloride ion concentration exacerbates the corrosion of the current collector and cathode material, limiting the compatibility of the electrolyte with the high-voltage cathode system. Furthermore, high concentrations of magnesium salts can increase electrolyte viscosity to some extent, further hindering rapid ion transport. Therefore, the concentration of the Lewis base can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, or 0.4 mol / L, or any range and sub-range between any two specific values mentioned above. It should be understood that in specific implementations, any of the above ranges can be combined with any other range, as long as the technical effects described in this application are achieved.
[0036] In some embodiments of this application, the concentration of the morpholine borane complex is 0.15 mol / L to 0.90 mol / L. As a core functional component for regulating solvation structure and inducing interfacial film formation, the concentration of the morpholine borane complex needs to be matched with the magnesium salt concentration to form a suitable reaction ratio. When the concentration of the morpholine borane complex is below 0.15 mol / L, the Lewis acid-base reaction between it and ethyl magnesium chloride cannot proceed sufficiently, making it difficult to construct a moderately coordinated boron-based magnesium active anion. The solvation sheath of magnesium ions cannot be effectively loosened, the desolvation energy barrier decreases only slightly, and the problem of high deposition / dissolution overpotential is difficult to fundamentally improve. Simultaneously, at low concentrations, there are insufficient boron-based precursors to participate in the interfacial reaction, making it impossible to form a continuous and dense composite SEI film on the magnesium anode surface. This makes it difficult to effectively block direct contact between the electrolyte and the magnesium anode, not only failing to adequately inhibit anode passivation but also increasing the proportion of unreacted magnesium chloride species in the system, exacerbating corrosion of the magnesium anode, and ultimately resulting in insignificant improvement in cycle stability. However, when the concentration of morpholinoborane complex exceeds 0.90 mol / L, excessive boron-based complexes will significantly increase the viscosity of the electrolyte system, significantly increase the bulk transport resistance of ions, and cause a decrease in the ionic conductivity of the electrolyte. This, in turn, increases the polarization of the battery at high current densities and deteriorates the rate performance. At the same time, excessive boron-based components will undergo excessive reduction and decomposition at the negative electrode interface, resulting in an excessively thick solid electrolyte interfacial film and increased interfacial impedance. This increases the resistance to magnesium ion transport across the interface and also causes irreversible consumption of electrolyte components, reducing the battery's first-cycle coulombic efficiency and capacity retention during cycling. In the electrolyte described in this application, the molar ratio of morpholine borane complex to ethyl magnesium chloride is (2:1) to (1:3), preferably greater than 1:1, and more preferably 2:1. Compared to the theoretical 1:1 ratio, the reactant equivalent of morpholine borane is actually in excess. However, this degree of excess allows morpholine borane to exert multiple synergistic advantages in the electrolyte: First, the amine borane containing NB coordination bonds, as a Lewis acid, can simultaneously anchor Mg in the electrolyte. 2+ The solvent THF weakens the interaction between strong ligands containing O and Cl and high charge density Mg. 2+ Strong interactions form Cl-containing - The loose magnesium solvation structure of THF effectively solves the problem of high desolvation energy barrier. Secondly, the presence of NB coordination bonds allows the 1,4-oxonitrogen hexacyclic amine boron anion to achieve a certain degree of electronic delocalization, weakening the coordination between magnesium ions and anions, reducing strong ion association, improving stability, and lowering the desolvation energy. Furthermore, the moderate rigidity of the 1,4-oxonitrogen hexacyclic ring helps to fix the orientation of the coordinating groups and reduce the entropy change in the desolvation process, while the larger steric hindrance of the ring weakens the interaction between the amine boron anion and Mg. 2+ The coordination strength of Mg is increased, thereby enhancing the coordination strength of Mg. 2+The diffusion kinetics and operating current density were analyzed. Finally, the excess amineborane acts as a dual additive at both the positive and negative electrodes. It can capture free water in the electrolyte, preventing passivation of the magnesium metal anode, and also adsorb onto the magnesium metal surface, helping to construct a favorable BN and CN bond SEI layer on the magnesium metal anode surface, improving magnesium ion conduction capacity, reducing the interfacial impedance of magnesium deposition / dissolution, and accelerating reaction kinetics. This novel magnesium-boron-based electrolyte provides a feasible and effective solution for achieving ultra-long cycle stability of magnesium batteries under high current density conditions. Therefore, the concentration of the morpholine borane complex can be 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, 0.85 mol / L, or 0.9 mol / L, or any range and sub-range between any two specific values mentioned above; the molar ratio of the morpholine borane complex to ethyl magnesium chloride can be 1:3, 1:2, 1:1, 1.5:1, or 2:1, or any range and sub-range between any two specific values mentioned above; it should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges, as long as the technical effect described in this application can be achieved.
[0037] II. A method for preparing a boron-based electrolyte for high-rate, low-overpotential magnesium batteries
[0038] Under an inert gas atmosphere, a Lewis base and an organic solvent are mixed and stirred. A morpholine borane complex is then added and stirred until homogeneous to obtain the boron-based electrolyte for the high-rate, low-overpotential magnesium battery. In the organic solvent, the concentration of the Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of the morpholine borane complex is 0.15 mol / L to 0.9 mol / L. The molar ratio of the morpholine borane complex to ethyl magnesium chloride can be in the range of (2:1) to (1:3).
[0039] In some embodiments of this application, the morpholine borane complex, Lewis base, and organic solvent are pretreated to ensure that the water content and oxygen content in the mixture are <0.01ppm and <0.01ppm, respectively.
[0040] III. Application of a boron-based electrolyte for high-rate, low-overpotential magnesium batteries
[0041] The high-rate, low-overpotential magnesium battery boron-based electrolyte described in this application, or the high-rate, low-overpotential magnesium battery boron-based electrolyte prepared by the aforementioned preparation method, is used to prepare rechargeable magnesium-ion batteries.
[0042] IV. Examples and Comparative Examples
[0043] Example 1
[0044] Step 1 Lewis acid pretreatment: Morpholin borane white powder is vacuum dried for 24 hours and then transferred to a glove box for sealed storage.
[0045] Step 2: Preparation of the electrolyte (2 mL): All reactions were carried out under an anhydrous and oxygen-free inert atmosphere. Weigh 121.1 mg of morpholine borane white powder into a dry glass bottle containing the electrolyte using an electronic balance. Then, use a pipette to add 1.5 mL of anhydrous tetrahydrofuran to the glass bottle. After the morpholine borane white powder is fully dissolved in the tetrahydrofuran, use a pipette to add 0.30 mL of ethyl magnesium chloride tetrahydrofuran solution (concentration of 2 mol / L) to the bottle. Bubbles were generated. Stir at room temperature for 8 hours to obtain a colorless, clear, and transparent electrolyte.
[0046] Example 2
[0047] This example is an adjustment to Example 1, except that the concentration of ethyl magnesium chloride is 0.1 mol / L and the molar concentration of the morpholine borane complex in the organic solvent is 0.15 mol / L. All other steps are exactly the same as in Example 1.
[0048] Example 3
[0049] This example is an adjustment to Example 2, except that the concentration of ethyl magnesium chloride is 0.4 mol / L. All other steps are exactly the same as in Example 1.
[0050] Example 4
[0051] The method is an adjustment based on Example 2, except that the molar concentration of the morpholine borane complex in the organic solvent is 0.9 mol / L. All other steps are exactly the same as in Example 1.
[0052] Example 5
[0053] This example is an adjustment to Example 1, except that the concentration of ethyl magnesium chloride is 0.4 mol / L and the molar concentration of the morpholine borane complex in the organic solvent is 0.9 mol / L. All other steps are exactly the same as in Example 1.
[0054] Example 6
[0055] This example is an adjustment to Example 1, except that the organic solvent is ethylene glycol dimethyl ether. All other steps are exactly the same as in Example 1.
[0056] Example 7
[0057] This example is an adjustment to Example 1, except that the organic solvent is tetraethylene glycol dimethyl ether. All other steps are exactly the same as in Example 1.
[0058] Comparative Example 1
[0059] The method is based on Example 1, but with the following adjustment: Lewis acid is replaced with pentafluorophenylboronic acid, and the molar ratio of EtMgCl to pentafluorophenylboronic acid is 1:1.
[0060] Step 3 Lewis acid pretreatment: After 24 hours of vacuum drying, pentafluorophenylboronic acid is transferred to a glove box for sealed storage.
[0061] Step 4: Preparation of the electrolyte (2 mL): All reactions were carried out under an anhydrous and oxygen-free inert atmosphere. Weigh 126 mg of pentafluorophenylboronic acid into a dry glass bottle containing the electrolyte using an electronic balance. Then, use a pipette to add 1.5 mL of anhydrous tetrahydrofuran dropwise to the glass bottle. After the pentafluorophenylboronic acid has fully dissolved in the tetrahydrofuran, use a pipette to add 0.30 mL of ethyl magnesium chloride (2 mol / L concentration) dropwise to the bottle. Bubbles were generated, and the mixture was stirred at room temperature for 8 hours to obtain a colorless, clear, and transparent electrolyte. The other steps were exactly the same as in Example 1.
[0062] Comparative Example 2
[0063] The method is based on Example 1, but with the following modifications: Lewis acid is replaced with (aniline)trifluoroboron, and the molar ratio of EtMgCl to (aniline)trifluoroboron is 1:1.
[0064] Step 3 Lewis acid pretreatment: (aniline) trifluoroboron is vacuum dried for 24 hours and then transferred to a glove box for sealed storage.
[0065] Step 4: Preparation of the electrolyte (2 mL): All reactions were carried out under an anhydrous and oxygen-free inert atmosphere. Weigh 118 mg of (aniline) trifluoroboron into a dry glass bottle containing the electrolyte using an electronic balance. Then, use a pipette to add 1.5 mL of anhydrous tetrahydrofuran dropwise to the glass bottle. After the (aniline) trifluoroboron is fully dissolved in the tetrahydrofuran, use a pipette to add 0.30 mL of ethyl magnesium chloride (2 mol / L concentration) dropwise to the bottle. Bubbles were generated, and the mixture was stirred at room temperature for 8 hours to obtain a colorless, clear, and transparent electrolyte. The other steps were exactly the same as in Example 1.
[0066] Comparative Example 3
[0067] The method is based on Example 1, but with the difference that Lewis base is replaced with phenyl magnesium chloride.
[0068] Step 2 Lewis base pretreatment: After vacuum drying for 24 hours, phenyl magnesium chloride is transferred to a glove box for sealed storage.
[0069] Step 4: Preparation of the electrolyte (2 mL): All reactions were carried out under an anhydrous and oxygen-free inert atmosphere. Weigh 121.1 mg of morpholine borane white powder into a dry glass bottle containing the electrolyte using an electronic balance. Then, use a pipette to add 1.5 mL of anhydrous tetrahydrofuran dropwise to the glass bottle. After the morpholine borane white powder is fully dissolved in the tetrahydrofuran, use a pipette to add 0.30 mL of phenyl magnesium chloride (concentration of 2 mol / L) dropwise to the bottle. Bubbles were generated, and the mixture was stirred at room temperature for 8 hours to obtain a colorless, clear, and transparent electrolyte. The other steps were exactly the same as in Example 1.
[0070] V. Performance Testing
[0071] The performance testing method for the electrolyte prepared in Example 1 is as follows. Other examples and comparative examples were tested using the same method. The test results of other examples are not significantly different from those of Example 1; therefore, Example 1 is used as an example for comparison and explanation.
[0072] (1) Coulombic efficiency test of reversible deposition / dissolution of magnesium
[0073] The reversible deposition / dissolution coulombic efficiency of the electrolyte prepared in the examples was tested using a constant current charge-discharge (GCD) tester. Testing was conducted by assembling CR2032 coin cells, with molybdenum foil (Mo) as the positive electrode current collector, polished magnesium sheet as the negative electrode, and glass fiber membrane (GF / A) as the separator. The assembled cells were allowed to stand at room temperature for at least 4 hours before testing. The charging cutoff voltage was 1.8V, and the current density and areal capacity ranged from 0.1 to 5.0 mA / cm². 2 .
[0074] The results obtained by testing the electrolyte prepared in the examples using the above methods are as follows:
[0075] The electrolyte prepared in Example 1 was at 0.5 mA cm⁻¹ -2 and 0.25 mAh cm -2 Under the given current conditions, the overpotential in the first cycle was 502 mV. After activation, the overpotential remained stable, and the overpotentials after 50, 500, 1000, and 1500 cycles were 193 mV, 229 mV, 254 mV, and 274 mV, respectively.
[0076] Table 1
[0077] Example 1 <![CDATA[0.5 mA cm -2 0.25 mAh cm -2 ]]> 193 99.9% 1500 Comparative Example 1 <![CDATA[0.5 mA cm -2 0.25 mAh cm -2 ]]> 248 98.2 859 Comparative Example 2 <![CDATA[0.5 mA cm -2 0.25 mAh cm -2 ]]> 199 93.7 808 Comparative Example 3 <![CDATA[0.5 mA cm -2 0.25 mAh cm -2 ]]> 370 98.7 372
[0078] like Figure 1 As shown in Table 1, Figure 1 The coulombic efficiency-cycle count curves visually reflect the long-cycle reversibility and lifespan of the electrolyte under high current density. During continuous deposition / dissolution cycles exceeding 1500 h, the battery coulombic efficiency remained stable close to the theoretical value, without significant fluctuations or efficiency drops. Comparing the data from the three comparative examples in Table 1, Comparative Example 1, which uses pentafluorophenylboronic acid instead of morpholine borane, has an average coulombic efficiency of only 98.2% and a cycle life shortened to 859 h; Comparative Example 2, which uses aniline trifluoroboron, has a coulombic efficiency as low as 93.7% and a cycle life of only 808 h; and Comparative Example 3, which uses phenyl magnesium chloride instead of ethyl magnesium chloride, has a coulombic efficiency of 98.7% and a cycle life of only 372 h. Furthermore, the area specific capacity-voltage curves at different cycle durations further demonstrate the low polarization characteristics and long-term interfacial stability of the electrolyte described in this application under high current density. During continuous deposition / dissolution cycles exceeding 1500 h, the battery coulombic efficiency remained stable at a level close to the theoretical value, without significant fluctuations or efficiency drops throughout the process. Based on the benchmark data from the three comparative examples in Table 1, Comparative Example 1, which used pentafluorophenylboronic acid instead of morpholine borane, had an average coulombic efficiency of only 98.2% and a cycle life shortened to 859 h; Comparative Example 2, which used aniline trifluoroboron, had a coulombic efficiency as low as 93.7% and a cycle life of only 808 h; and Comparative Example 3, which used phenyl magnesium chloride instead of ethyl magnesium chloride, had a coulombic efficiency of 98.7% and a cycle life of only 372 h. This dynamic process characterization and quantitative cross-sectional comparison demonstrate that the composite system constructed by ethyl magnesium chloride and morpholine borane in this application can effectively regulate the interfacial reaction pathway of the magnesium anode: chloride ions generated by the dissociation of ethyl magnesium chloride can selectively adsorb on the anode surface, inhibiting the irreversible reduction and decomposition of solvent molecules; morpholine borane preferentially undergoes reduction at the anode interface, constructing a composite solid electrolyte interfacial film containing both inorganic and organic heterocyclic components, blocking direct contact between the electrolyte and the magnesium anode, and inhibiting the continuous formation of the insulating passivation layer. Under the combined effect of these two components, the ineffective consumption of active magnesium and the accumulation of by-reaction products during cycling are significantly suppressed, and the reversibility of magnesium deposition / dissolution is greatly improved, thus specifically solving the technical problems of poor cycle reversibility, short lifespan, and easy passivation of the anode in existing boron-based magnesium electrolytes.
[0079] This application further discovers a positive synergistic enhancement effect between the two aforementioned performance aspects. The near-theoretical high coulombic efficiency means that interfacial side reactions are suppressed to the maximum extent, and high-impedance passivation products are not continuously generated during cycling, providing a structural basis for the long-term stability of interfacial impedance and ensuring a gradual increase in overpotential during ultra-long cycling. Conversely, the lower desolvation energy barrier and the low polarization characteristics brought about by the high-conductivity interfacial film weaken the driving force for electrolyte component decomposition under high current and high potential, further reducing the occurrence of irreversible side reactions and consolidating the high coulombic efficiency during cycling. The performance imbalance commonly observed in the three comparative studies in Table 1—namely, the system with a high overpotential generally has a shorter cycle life, while the system with a low overpotential shows a significant decrease in coulombic efficiency—precisely demonstrates the synergistic effect of solvation structure regulation and interfacial film modification in the system of this application. These two approaches, respectively addressing bulk ion transport kinetics and interfacial reaction stability, achieve simultaneous improvement in three core performance parameters—coulombic efficiency, cycle life, and overpotential—through positive coupling, rather than sacrificing one performance parameter to optimize another. Ultimately, this endows the electrolyte with comprehensive performance that balances ultra-long cycle life, high reversibility, and low polarization at moderate current densities, systematically solving the technical problem that existing boron-based magnesium electrolytes cannot simultaneously meet multi-dimensional performance requirements.
[0080] (2) Stability test of magnesium deposition / dissolution oxidation
[0081] The electrolyte prepared in the examples was tested for magnesium reversible deposition / dissolution coulombic efficiency and oxidative stability using cyclic voltammetry (CV) and linear voltammetry (LSV), respectively. The tests were conducted using assembled CR2032 coin cells, with a stainless steel (Mo) positive electrode current collector, a magnesium sheet negative electrode, and a glass fiber membrane (GF / A) separator. The LSV voltage range was from open-circuit voltage to 5.0 V, and the scan rate was 5 mV / s.
[0082] The oxidation initiation potentials of the electrolyte prepared in the examples on Cu, SS, CF, and Mo current collectors were 2.32 V, 2.67 V, 3.01 V, and 3.10 V, respectively, compared to Mg / Mg. 2+ The result is as follows Figure 2As shown, this result demonstrates that the electrolyte of this application effectively broadens the anodic oxidation stability window, specifically addressing the technical problems of low oxidation stability and difficulty in adapting to high-voltage cathode systems in existing simple borohydride magnesium electrolytes. This performance improvement stems from the system's component design and solvation structure regulation: morpholine borane, as a nitrogen-containing heterocyclic coordinated borane complex, possesses a low molecular orbital energy level. The boron-based active anion generated by its Lewis acid-base reaction with ethyl magnesium chloride has a higher oxidation decomposition potential, fundamentally enhancing the electrolyte's antioxidant capacity. Simultaneously, the coordination structure formed by the two can compete for magnesium ion solvation sites, reducing the proportion of free ether solvent molecules in the system, weakening the tendency of solvent molecules to oxidize and decompose at high potentials, and further consolidating the electrolyte's anodic stability. Compared to traditional simple borohydride electrolytes, this system shows a significant improvement in oxidation potential on molybdenum and carbon-based inert current collectors, providing a feasible electrolyte-level basis for subsequent matching of cathode materials with higher operating potentials and improving the energy density of magnesium battery systems. Meanwhile, the improved oxidation stability, combined with the interface regulation effect on the negative electrode side, forms a two-way synergy, jointly enhancing the overall long-cycle performance of the electrolyte. The composite solid electrolyte interface film induced by morpholine borane on the negative electrode surface ensures the high reversibility and low polarization of the magnesium deposition / dissolution process, avoiding the continuous occurrence of side reactions on the negative electrode side and the accumulation of the insulating passivation layer; while the wider oxidation window on the positive electrode side inhibits the oxidative decomposition and by-product deposition of the electrolyte at high potentials during long-cycle operation, reducing the irreversible consumption of active components and the continuous increase in interface impedance on the positive electrode side. Both maintain the structural and interface stability of the electrolyte across the entire charge-discharge voltage range from the positive and negative electrodes, respectively, mutually supporting each other to ensure high coulombic efficiency and stable polarization levels during long-cycle operation, further mitigating the problem of rapid performance degradation caused by the synergistic aggravation of side reactions at both electrodes during the cycling process of existing electrolytes. Meanwhile, the difference in oxidation potential on different current collectors also clarified the current collector compatibility range of this electrolyte. Its excellent compatibility with molybdenum and carbon-based current collectors can be adapted to the conventional testing system of magnesium half-cells. At the same time, it provides a basis for the selection of subsequent positive electrode current collectors and avoids premature electrolyte failure caused by current collector corrosion or catalytic decomposition.
[0083] (3) Magnesium ratio performance test
[0084] The rate performance of the electrolyte prepared in the examples was tested using a constant current charge-discharge (GCD) method. The tests were conducted by assembling CR2032 coin cells, with magnesium sheets as the positive and negative electrodes and a glass fiber membrane (GF / A) as the separator. GCD charge-discharge tests were performed at a current density of 0.1 mA cm⁻¹. -2 ~10 mA cm -2 ~1 mA cm -2 .
[0085] In practical applications, the electrolyte prepared in the examples exhibits current densities ranging from 0.1 mA cm⁻¹. -2 up to 10.0 mAcm -2 Then it decreased to 1.0 mA cm⁻¹ -2 Mg|EMOB|Mg symmetric cell at 0.1 mA cm -2 The overpotential is as low as 45 mV at current densities, and the maximum rate capability is up to 10.0 mA cm⁻¹. -2 The overpotential was only 490 mV, and the symmetrical battery did not short-circuit throughout the entire cycle. This indicates that the battery can maintain stable cycling under the corresponding current density, exhibiting good rate performance. Figure 3 As shown in the figure. This result demonstrates that the electrolyte of this application possesses excellent rate tolerance and rapid ion transport kinetics, specifically addressing the technical problems of rapid polarization increase and poor rate performance of existing magnesium electrolytes under high current densities. This performance stems from the combined effect of optimized bulk solvation structure and improved interfacial transport characteristics: the chloride ions provided by ethyl magnesium chloride synergistically regulate the coordination of magnesium ions with morpholine borane and its anions, forming a loose solvation sheath layer of magnesium ions, reducing the desolvation energy barrier, accelerating the bulk ion transport rate, and weakening activation polarization and concentration polarization under high current charge and discharge from the perspective of reaction kinetics; at the same time, the CN and BN high ionic conductivity composite solid electrolyte interfacial film induced by morpholine borane on the negative electrode surface can provide a smooth cross-interfacial transport channel for magnesium ions, avoiding polarization abrupt changes caused by interfacial mass transfer hindrance under high current. Meanwhile, this rate performance and the aforementioned long-cycle stability and high coulombic efficiency have a positive and mutually supportive relationship. It can adapt to solvated structures and interfacial films with ultra-high current densities, and possesses excellent structural stability, which can continuously maintain ion transport capabilities during long cycles, ensuring stable polarization and high reversibility during cycling. Conversely, the stability and non-deterioration of the interfacial structure during long cycles also enable the electrolyte to maintain stable rate performance throughout its entire life cycle, without a continuous decline in rate tolerance as cycling progresses. Together, these two factors endow the electrolyte with wide current range applicability, enabling it to achieve ultra-long stable cycling at low currents as well as support high-rate charge and discharge conditions, thus expanding the application scenarios of the electrolyte.
[0086] (4) Full battery rate performance test
[0087] The electrolyte prepared in the examples was used to test the rate performance of a full-cell constant current charge-discharge cycle. The test was conducted using a CR2032 coin cell symmetric battery, with CuS as the positive electrode, carbon paper (CF) as the substrate, a magnesium sheet as the negative electrode, and a glass fiber membrane (GF / A) as the separator. The current was 50 mA g. -1 -200 mA g -1 -50 mA g-1 .
[0088] The Mg||CuS full cell assembled with the electrolyte prepared in the examples, at 50 mA g -1 At current density, the discharge specific capacity of the CuS cathode reaches 246 mAh g. -1 The current density was increased to 200 mA g. -1 Afterwards, the discharge specific capacity reached 102 mAh g. -1 When the current density returns to 50 mA g -1 At that time, the discharge specific capacity of CuS can be restored to 235 mAh g. -1 This indicates that the Mg|EMOB|CuS full cell possesses good rate performance, such as... Figure 4 As shown in the figure, this result verifies that the electrolyte of this application possesses excellent comprehensive electrochemical performance in a practical full-cell system, solving the technical problems of existing magnesium electrolytes being unable to simultaneously achieve high specific capacity and excellent rate performance in full cells, as well as rapid capacity decay under high current. This performance relies on the multi-dimensional optimization effect of the electrolyte: the wider oxidation stability window of the electrolyte can adapt to the working potential range of the CuS cathode, suppressing the oxidative decomposition of the electrolyte on the cathode side during charging and discharging, reducing the irreversible consumption of active components and the accumulation of cathode interface impedance; the optimized ion transport kinetics at the bulk level can support the rapid insertion and extraction reaction of magnesium ions on the cathode side, ensuring capacity performance under high current density; the stable composite interface film on the anode side avoids the increase in full-cell internal resistance caused by anode passivation and side reaction accumulation, maintaining the structural stability of the full-cell during rate testing. Moreover, the performance of this full cell forms a logically linked layer-by-layer verification with the test results of half-cell and symmetric cells. The negative electrode-side rate polarization characteristics verified by the symmetric cell, together with the deposition / dissolution reversibility verified by the half-cell, form the basis of the full-cell performance. The test results of the full cell further demonstrate the performance advantages of the half-cell system in actual battery systems, indicating that the electrolyte described in this application is not only effective in ideal half-cell systems, but can be matched with conventional magnesium storage cathodes and achieve stable electrochemical performance, providing direct experimental support for the practical application of the electrolyte system described in this application.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of this application without departing from the spirit and scope of this application should be covered within the scope of the claims of this application.
Claims
1. A boron-based electrolyte for high-rate, low-overpotential magnesium batteries, characterized in that, The electrolyte is composed of a morpholine boronane complex, a Lewis base, and an organic solvent; the structural formula of the morpholine boronane complex is as follows: ; In the organic solvent, the concentration of Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of morpholine borane complex is 0.15 mol / L to 0.9 mol / L.
2. The boron-based electrolyte for high-rate, low-overpotential magnesium batteries according to claim 1, characterized in that, The morpholine borane complex is morpholine borane.
3. The boron-based electrolyte for high-rate, low-overpotential magnesium batteries according to claim 1, characterized in that, The Lewis base is ethyl magnesium chloride.
4. The boron-based electrolyte for high-rate, low-overpotential magnesium batteries according to claim 1, characterized in that, The organic solvent is at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, or 2-methyltetrahydrofuran.
5. A method for preparing a boron-based electrolyte for a high-rate, low-overpotential magnesium battery, characterized in that, The specific steps for preparing the boron-based electrolyte for high-rate, low-overpotential magnesium batteries according to any one of claims 1 to 4 are as follows: After mixing and stirring Lewis base and organic solvent under an inert gas atmosphere, morpholine borane complex is added to react and stirred evenly to obtain the boron-based electrolyte for high-rate, low-overpotential magnesium battery. In the organic solvent, the concentration of the Lewis base is 0.1 mol / L to 0.4 mol / L, and the concentration of the morpholine borane complex is 0.15 mol / L to 0.9 mol / L; the molar ratio of the morpholine borane complex to ethyl magnesium chloride is (2:1) to (1:3).
6. The preparation method according to claim 5, characterized in that, The morpholine borane complex, Lewis base, and organic solvent were pretreated to ensure that the water content and oxygen content in the mixture were <0.01 ppm and <0.01 ppm, respectively.
7. An application of a boron-based electrolyte for high-rate, low-overpotential magnesium batteries, characterized in that, The high-rate, low-overpotential magnesium battery boron-based electrolyte according to claims 1-4 or the high-rate, low-overpotential magnesium battery boron-based electrolyte prepared by the preparation method according to claim 5 or 6 is used to prepare rechargeable magnesium-ion batteries.